Encoding information : unique Natufian objects from Hayonim Cave, Western Galilee, Israel - Bar-Yosef, O.
New incised bone and limestone Natufian objects discovered during the 1997 season of excavations at Hayonim cave (Western Galilee, Israel), as well as a bone object found earlier in Kebara cave (Mount Carmel), indicate direct connections between the two sites. The incised pattern on the slab is interpreted as supportive evidence for emerging territoriality among Natufian communities in the Levant.